The Impact of Financial Technology on Banking Profitability - Hisyam Haris Nugroho; FX Sugiyanto (Universitas Persada Indonesia YAI, 2023)
This study aims to explain the impact of financial technology (Fintech) on banking profitability and examine differences in banking profitability along with the growth of Fintech. The test is carried out using an event study, while Profitability is measured using financial ratios, namely ROA, ROE, and BOPO. The data used in this study is 2012-2017 in state-owned banks with the highest total assets that have fintech services (Bank Mandiri, BRI, BNI, BCA, DANAMON, CIMB, OCBC, BTPN, BUKOPIN, and Bank PERMATA).The methodology used is a descriptive quantitative approach by conducting different tests and to explain the relationship between these variables, multiple linear r egression tests are used. Different tests are carried out to see whether banking profitability is disrupted by the fintech phenomenon or not. Quantitative analysis is carried out by examining related problems. The conclusion that can be drawn is that innovations that occur in banking through the fintech phenomenon are not as a distraction but as an opportunity to develop fintech services and increase banking profitability.